Presenting a Model for Organizational Ambidexterity in Tejarat Bank of Isfahan Using Combined Methods of Grounded Theory and Fuzzy Delphi - Masoud Vahedi; Hossein Panahian; Hassan Ghodrati; Mohsen Rasolian (مدیریت بهره وری, 2022)
The purpose of this study was to design an organizational ambidexterity model in the branches of Tejarat Bank in Isfahan, identifying important indicators. The research method was a sequential combination of exploratory case study and survey. Grounded theory and Lisrel software were used to confirm the identified organizational ambidexterity model and test the hypotheses. Based on the initial findings of the grounded theory technique, 74 indicators remained after the initial screening and removal of duplicate and redundant codes. These indicators were introduced as the input data of fuzzy Delphi technique and finally 18 indicators were considered to continue the process and present the main and sub-themes. The organizational ambidexterity model and its identified importance for generalization to the whole complex were confirmed by the structural equation approach (exploratory factor analysis). Human resource indicators of the two-dimensional organizational model, which mainly refers to the organizational and individual cultures, show the influential role of the internal characteristics of individuals and organizations in the implementation of a new concept. Among strategic indicators the emphasis was on the existence of a flexible structure to implement dual power. In terms of social capital, a significant point was the high priority of the index of reviewing social processes and components in the total indicators of the ambidextrous organization. This means that in the early stages of implementing dual power, it is necessary to review the processes and equipment to discover exploitation and exploration opportunities, plan to pursue these opportunities simultaneously, and develop an ambidextrous model in different parts of the bank.